Early venous congestion after diep flap breast reconstruction: case report of a successful management - Baccarani, Alessio; Starnoni, Marta; Pappalardo, Marco; Lattanzi, Melba; Blessent, Claudio Gio Francesco; De Maria, Federico; De Santis, Giorgio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: More than 250 000 women estimated to be diagnosed with breast cancer in the USA every year. Mastectomy is primary treatment for more than a third of those with early-stage disease. Most of the patients undergoing mastectomy receive breast reconstruction. A number of. Surgical techniques have been described to reconstruct the breast. With autologous tissue breast reconstruction, the plastic surgeon uses patient’s own tissues, taken from a different part of the body where there is an excess of fat and skin. Deep inferior epigastric perforator (DIEP) flap is the autologous breast reconstruction technique of choice in our department due to long lasting results, low donor site morbidity and positive patient reported outcomes have been described. Case Report: We present the case of a 42-year-old woman who underwent neoadjuvant chemotherapy followed by left breast simple mastectomy, axillary lymph-nodes dissection and later adjuvant radiation therapy (RT). After conclusion of RT a DIEP flap breast reconstruction was performed. Nine-hours after the operation, signs of acute venous congestion were noted. The venous congestion was treated by a combined surgical and medical approach based on pedicle discharge and ICU resuscitation protocol. After take back surgery, the patient was tightly monitored in the intensive care unit where intravenous heparin infusion and leech therapy were performed for 2 days. Flap congestion resolved completely, and the patient was discharged. Conclusions:Venous congestion is very difficult to treat due to its potential multifactorial nature. The most important step is to recognize this kind of emergency because irreversible microvascular damages will develop in 6–8 hours. Because of multiple causes of venous congestion a timely multidisciplinary approach is mandatory, to maximize flap salvage and success rates.